Ứng dụng đại số gia tử đốl sánh các giá trị ngôn ngữ - Khang, Trần Đình (Journal of Computer Science and Cybernetics, 2016)
This paper interpretes some methods for comparison of linguistic values. There are the aggregation of hedge algebras, the if-then rules and the distance table between linguistic values. It can be used for linguistic reasoning in practical problems.